1996
DOI: 10.1007/bf00005038
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cycles and microhabitat use in two species of topminnow, Fundulus olivaceus and F. euryzonus, from the southeastern United States

Abstract: SynopsisDifferences in spawning seasonality, inferred from ovarian cycles, and microhabitat use for two closely related Fundulus species were not effective as potential reproductive isolating mechanisms. Seasonal spawning periodicity of E olivaceus and E euryzonus as shown by changes in mean egg diameter and mean number of mature eggs recovered from ovaries showed nearly identical temporal patterns in reproductive activity. Peak egg development was between April and May and was lowest by the end of August. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 7 publications
0
28
1
Order By: Relevance
“…Thomerson (1966) observed the viability and fertility of lab reared F1 hybrids (between F. notatus and F. olivaceus) and concluded that prezygotic isolating mechanisms (behavioral and ecological differences) were dominant. A number of other authors have cited Thomerson's (1966) data on the viability of hybrids (Braasch and Smith 1965;Setzer 1970;Howell and Black 1981;Blanchard 1996) in coming to similar conclusions about the importance of prezygotic isolating mechanisms. However, in the only study to rear multiple generations of hybrids, Cuca (1976) reported high egg mortality for lab reared F2 progeny (F. notatus-F. olivaceus crosses) but lacked appropriate sample sizes to come to any conclusions.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Thomerson (1966) observed the viability and fertility of lab reared F1 hybrids (between F. notatus and F. olivaceus) and concluded that prezygotic isolating mechanisms (behavioral and ecological differences) were dominant. A number of other authors have cited Thomerson's (1966) data on the viability of hybrids (Braasch and Smith 1965;Setzer 1970;Howell and Black 1981;Blanchard 1996) in coming to similar conclusions about the importance of prezygotic isolating mechanisms. However, in the only study to rear multiple generations of hybrids, Cuca (1976) reported high egg mortality for lab reared F2 progeny (F. notatus-F. olivaceus crosses) but lacked appropriate sample sizes to come to any conclusions.…”
Section: Introductionmentioning
confidence: 68%
“…While some contend that syntopic populations are rare (Thomerson 1966;Thomerson and Woolridge 1970), reports of sympatry and occurrence of hybrid individuals is not uncommon (Setzer 1970;Thomerson and Woolridge 1970;Cuca 1976;Howell and Black 1981;Blanchard 1996;Duvernell et al 2007). Examination of records from some of the largest ichthyological collections in the region indicate contact zones in at least 17 separate drainages throughout the ranges of the three species (Schaefer, unpublished data).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar classification was used by Blanchard (1996) for categorizing eggs of blackspotted topminnow, Fundulus olivaceus, and broadstripe topminnow, F. euryzonas. We counted the number of eggs in each category and measured diameters using an ocular micrometer (40·) in a compound microscope.…”
Section: Short-term Behavioral Studymentioning
confidence: 99%
“…The Fundulus notatus species complex is comprised of the Blackstripe Topminnow (F. notatus) the Blackspotted Topminnow (F. olivaceus) and the Broadstripe Topminnow (F. euryzonus) that all share similar niches (Thomerson and Woolridge 1970;Blanchard 1996) and occasionally hybridize in contact zones found throughout their ranges (Thomerson 1967;Setzer 1970;Duvernell et al 2006;Schaefer et al 2009) (Fig. 2).…”
Section: Introductionmentioning
confidence: 98%